(untitled) (Economics and region, 2018)
The article analyzes the formation of an economic opinion of the founders of the first Ukrainian cooperative «National Trade». The basic economic and educational activities of the cooperative «National Trade» and its impact on the financial, economic and cooperative education of western Ukraine. The main problem of the cooperative and the key benefits of the cooperative type of organization of the trade processes in the territories of western Ukraine during the late XIX – early XX century were discussed. An important practical orientation and the special relevance of this study we believe is the search of the priorities in the development of educational achievements of the first Ukrainian cooperative «National Trade», which ultimately significantly influenced the development of education of the population, and in terms of modernity left a great legacy in the direction of economic and cooperative education in Western Ukraine during the late nineteenth and early twentieth century. Problems of formation and development of cooperative and economic education are reflected in the works of scientists, in particular, such as I.L. Gorokhovskyi, N. Bila, G. Bilavych, Z. Brodyk, Z. Werbowyi, A. Vypasnyak, V. Visyn, S. Helei, N. Lubkovych, V. Motsyuk, I. Potapyuk, L. Potapyuk, B. Stuparyk, O. Himyak, V.P. Recrut, K.P. Chokan, L. Lavrik-Slisenko, Z.V. Hipters, E.L. Lortykyan, E.L. Soshynska, T.M. Zavora, I. Novikova, S. Zlupko, I. Zulyak, K. Kondratyuk and others. However, the case remains open - how to make economic and cooperative education more modern, popular among young people, how to satisfy the needs of society for qualified experts and minimize negative processes that hinder the improvement of economic education in Western Ukraine. Our main task is to explore the contribution and achievements of the first Ukrainian cooperative «National Trade» and the events which, in our opinion, mostly influenced the further successful development of economic and cooperative education in Western Ukraine during the late nineteenth and early twentieth century. Summarizing the research, it is worth noting that the first Ukrainian cooperative «National Trade» has left a huge scientific heritage and made a significant mark for economic development and cooperative education, by providing an economic knowledge base in teaching in expert schools. We thoroughly reviewed the educational achievements of the first Ukrainian cooperative «National Trade» and its contribution to economic development and cooperative education in Western Ukraine (second half of XIX – early XX centuries)